An improved high-order ISPH method for simulation of free-surface flows and convection heat transfer - Garoosi, Faroogh; Shakibaeinia, Ahmad (Powder Technology, 2020)
Keywords: Ahmad_Shakibaeinia

Numerical simulation of free-surface flow and convection heat transfer using a modified Weakly Compressible Smoothed Particle Hydrodynamics (WCSPH) method - Garoosi, Faroogh; Shakibaeinia, Ahmad (International Journal of Mechanical Sciences, 2020)
Keywords: Ahmad_Shakibaeinia

A WCSPH Particle Shifting Strategy for Simulating Violent Free Surface Flows - Krimi, Abdelkader; Jandaghian, Mojtaba; Shakibaeinia, Ahmad (Water, 2020)
In this work, we develop an enhanced particle shifting strategy in the framework of weakly compressible δ+-SPH method. This technique can be considered as an extension of the so-called improved particle shifting technology (IPST) proposed by Wang et al. (2019). We introduce a new parameter named “ϕ” to the particle shifting formulation, on the one hand to reduce the effect of truncated kernel support on the formulation near the free surface region, on the other hand, to deal with the problem of poor estimation of free surface particles. We define a simple criterion based on the estimation of particle concentration to limit the error’s accumulation in time caused by the shifting in order to achieve a long time violent free surface flows simulation. We propose also an efficient and simple concept for free surface particles detection. A validation of accuracy, stability and consistency of the presented model was shown via several challenging benchmarks.
Keywords: Ahmad_Shakibaeinia